1994
DOI: 10.1002/1520-6629(199410)22:4<359::aid-jcop2290220408>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Citizen participation in prevention activities: A path model

Abstract: Success in the recent shift in focus of alcohol and other drug (AOD) prevention programs to comprehensive community models requires widespread citizen participation. Few studies, however, have examined the factors that affect individual participation in the area of AOD prevention. Building upon the citizen participation literature from a variety of non‐AOD substantive areas, this study hypothesizes and examines a path model composed of three constructs that may affect participation: participation accessibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…For example, Kauffman and Poulin (1994) found that by showcasing the success of substance abuse prevention efforts to research participants, they were more likely to participate in other prevention programs in the community. To that end, Peterson and Reid (2003) suggested that prevention researchers ought to communicate the effectiveness of programs in ways that will encourage community members to participate.…”
Section: Developing Ethnic Identitymentioning
confidence: 92%
“…For example, Kauffman and Poulin (1994) found that by showcasing the success of substance abuse prevention efforts to research participants, they were more likely to participate in other prevention programs in the community. To that end, Peterson and Reid (2003) suggested that prevention researchers ought to communicate the effectiveness of programs in ways that will encourage community members to participate.…”
Section: Developing Ethnic Identitymentioning
confidence: 92%
“…A critical component of empowerment theory, which can be targeted by prevention planners, is the participatory process engaged in by individuals as they work to improve the quality of lives in their communities~Gutiérrez, 1995; Kieffer, 1984;Lord, Ochocka, Czarny, & MacGillivary, 1998; Although examples of successful efforts to promote citizen participation in substance abuse prevention initiatives exist~e.g., Daley & Marsiglia, 2000;Kauffman & Poulin, 1994;Poulin & Kauffman, 1995!, additional research is needed to explicitly examine the principles that anchor relationships between citizen participation and empowerment in substance abuse prevention and other related community contexts~Zimmerman, 2000!. To date, no formal theory exists that adequately explains the mechanisms by which individuals, organizations, and communities become empowered~Gutiérrez, Glen-Maye & DeLois, 1995;Price, 1990;Wandersman & Florin, 2000!.…”
mentioning
confidence: 99%
“…Kauffman and Poulin [3] examined a stratified random countywide sample of 1,019 adult citizens in the eastern part of the U.S. to ascertain which of the following factors influenced individual participation in substance abuse prevention activities: Participation accessibility, desire to participate, and knowledge about participation. Perceived efficacy ("knowledge") of prevention programs was found to be the strongest predictor of citizen participation, suggesting that programs might develop strategies (media campaigns) to demonstrate the utility of their programmatic activities to the community.…”
Section: Literature Review Factors Contributing To Citizen Participationmentioning
confidence: 99%
“…Perceived efficacy ("knowledge") of prevention programs was found to be the strongest predictor of citizen participation, suggesting that programs might develop strategies (media campaigns) to demonstrate the utility of their programmatic activities to the community. Kauffman and Poulin [3] were also interested in investigating the socio-demographic factors that affected participation in economically and socially disorganized communities. Consistent with previous findings, knowledge had the strongest direct effect on participation, with desire and accessibility adding important indirect effects.…”
Section: Literature Review Factors Contributing To Citizen Participationmentioning
confidence: 99%
See 1 more Smart Citation